Binding of cholesterol and bile acid to hemicelluloses from rice bran. (June 2013) - Hu, Guohua; Yu, Wenjian
<x xml:space="preserve">Abstract</x> The objective of this study was to investigate the possibility of using hemicellulose from rice bran to scavenge cholesterol and bile acid in vitro study. This paper demonstrates that rice bran hemicellulose A (RBHA), rice bran hemicellulose B (RBHB) and rice bran hemicellulose C (RBHC) have the potential for binding cholesterol and bile acid. The quantity of cholesterol and bile acid bound varies from one rice bran fibre to another. As it can be inferred from the results of the study, RBHB was characterized by the highest capacity for cholesterol binding, followed by RBHC and RBHA. Binding of cholesterol and bile acid to rice bran insoluble dietary fibre (RBDF) and cellulose from rice bran was found to be poor. Lignin from rice bran was the least active fraction for binding cholesterol and bile acid. This confirms that the RBHB preparation from defatted rice bran has great potential in food applications, especially in the development of functional foods.